The Dialectics of Traditional and Modern Islamic Education in Banten: A Study of KH Ahmad Rifa'i Arief’s Leadership and the Relevance of Mohammad Natsir’s Educational Thought (1990–1999) - Weny Widyawati Bastaman; Yon Machmudi; Didik Pradjoko (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study aims to analyze the dialectic between traditional and modern Islamic education in Banten through a study of the leadership of KH. Ahmad Rifa’i Arief during the period 1990–1999, as well as the relevance of Mohammad Natsir’s educational thought in its development. Islamic educational institutions in Banten have a long history. In Banten, traditional Islamic boarding schools (pesantren) play a significant role in shaping the character of society. On the other hand, the rapidly developing currents of modernization and globalization demand that education undergo transformation in terms of systems and institutions. This study employs a qualitative method with a historical approach and a biographical study, relying on primary sources—namely interviews with the family, colleagues, and alumni of KH. Ahmad Rifa’i Arief—as well as secondary sources from relevant literature. The results of this study indicate that the leadership of KH. Ahmad Rifa’i Arief brought about reforms in Banten regarding pesantren traditions and modern education through the integration of religious and general curricula. Furthermore, Mohammad Natsir’s ideas on integral education are closely related to the educational concepts proposed by Kyai Rifa’i. Therefore, this study affirms that the educational model developed by KH. Ahmad Rifa’i Arief contributed to the renewal of Islamic education in Banten and remains relevant for the development of pesantren in the contemporary era.